Paradygmat partycypacyjny w naukach społecznych. Wykorzystywanie danych wytworzonych przez badanych w analizie jakościowej = Participatory paradigm in social sciences. Use of data produced by qualitative analysis respondents - Bielecka-Prus, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the research process not only the data gathered by researchers (e.g. observations) or with the help of informants (various types of interviews) is useful but also the one which was independently collected by respondents. They may include various types of personal documents, the studies with a long tradition in Poland, but also the methods more rarely used by researches: diary interviews, projects based on the cooperation in visual research or systematic self-observation. The article discusses main methodological principles of participatory research as well as advantages and drawbacks of this research method.
Keywords: nauki społeczne; badania partycypacyjne